Cross-cultural adaptation to Brazilian Portuguese of the Michigan Neuropathy Screening Instrument: MNSI-Brazil - Franassis Barbosa de Oliveira; Kárenn Klycia Pereira Botelho; Arthur Rodrigues Bezerra; Diego Igor de Oliveira Azevedo; Clarissa Cardoso dos Santos-Couto-Paz; Emerson Fachin-Martins (Arquivos de Neuro-Psiquiatria)
ABSTRACT Since 1994, the University of Michigan Diabetes Research and Training Center proposed an instrument to measure neuropathies not yet adapted to use in Brazil. Then, this study aimed to adapt cross-culturally the Michigan Neuropathy Screening Instrument (MNSI) into Brazilian Portuguese, verifying its reliability. Thirty diabetic patients were initially evaluated with the adapted version after completed the essential steps to accomplish the cross-cultural adaptation. Twenty-two of them completed the procedures to repeat the measured scores after day 1 (trial 0). The repeated measurements were tested at days 2 or 3 (trial 1) by another rater (inter-rater reliability) and retested at day 20 (trial 2) by one of the attended raters (inter-test reliability). There were not great semantics, linguistics or cultural differences between two versions and excellent reliability was confirmed by intra-class correlation coefficient above 0.840. It was concluded that MNSI in the Brazilian version is reliable and it is ready to use.